FunAR-furniture augmented reality application to support practical laboratory experiments in interior design education - Fairuz Iqbal Maulana; Baskoro Azis; Tiara Ika Widia Primadani; Pangeran Rasyach Artha Hasibuan (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Practical learning in the laboratory has been limited due to the COVID-19 pandemic. Conventional education must adapt to increasingly digital technological developments. The design of interactive learning media with augmented reality technology can be a solution and support the previous conventional learning. FunAR is a Furniture Augmented Reality Application developed using the analysis, design, development, implementation, and evaluation (ADDIE) method consisting of ADDIE. In its implementation, the FunAR application will provide basic information about existing equipment in Lab Furniture, accompanied by 2D images, and augmented reality technology that creates 3D objects from each piece of equipment in Lab Furniture. From 15 student respondents, the results reveal that distance, angle, and device specifications significantly impact camera marker reading. A distance of 20 cm to 80 cm and an angle of 25° to 100° can display 3D objects. Likewise, the camera’s ability to process reading markers is better on smartphones with better hardware specifications. The results of the respondents showed that 80% of respondents were satisfied with the FunAR application.